Challenging times: Delivering gene therapies and an opportunity for shared learning - Kennedy, Cormac; Hennessy, Martina (My University, 2021)
As we embrace the era of precision medicine, gene therapies are the vanguard in the fight to cure rare diseases. While rare diseases are just that, rare, it is suggested that patients with rare diseases worldwide outnumber those with HIV and cancer combined.1 The development of safe and effective therapies that target genetically driven diseases has progressed significantly since the initial controversies. Now that gene therapies have moved from bench to bedside and achieved regulatory approval, a pipeline of therapies exists providing much needed hope for patients with incurable rare diseases. However, processes to customize the administration of these therapies in a safe, patient-centred and efficient manner are necessary for health care systems. Our recent experience delivering gene therapies, and Zolgensma® specifically, involved many challenges, not least an unprecedented COVID-19 pandemic. Following the recent themed issue on Advanced Therapies in this journal, our experience provides an opportunity to share lessons with international centres who will deliver these therapies.
PUBLISHED